Introduction to wood and natural fiber composites - Stokke, Douglas D.; Wu, Qinglin; Han, Guangping (Chichester, West Sussex, United Kingdom : Wiley, 2014)
"Bringing together widely scattered information on the fundamental concepts and technological applications for the manufacture of wood and natural fiber composites, this reference provides a much needed overview of this rapidly evolving field in a way that is accessible for advanced undergraduates, graduate students, and practicing professionals alike. After first covering the fundamental concepts, the book then moves on to discuss technical applications and finally concludes with a discussion on environmental considerations, sustainability, and methods of evaluating product properties and performance"--
"This book brings together widely scattered information on fundamental concepts and technological applications for the manufacture of wood- and natural fiber composites, providing a much needed and accessible overview of this rapidly evolving field"--
3.7 Wood Is the Exemplar: Extending Principles to Other Plant MaterialsReferences; 4 Consolidation Behavior of Lignocellulosic Materials; 4.1 Introduction; 4.2 Synthetic Crystalline and Amorphous Polymers; 4.2.1 Polyethylene; 4.2.2 Polystyrene: Isotactic, Syndiotactic, and Atactic; 4.2.3 Degree of Crystallinity, Revisited; 4.2.4 Thermal Softening of Amorphous Polymers: Glass Transition Temperature, Tg; 4.3 Glass Transition Temperature of Wood Polymers; 4.3.1 Glass Transition Temperature of Wood Polymers: Empirical Data; 4.3.2 Kwei Equation: Modeling Tg of Wood Polymers.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Engineered wood; Composite materials; Natural products; SCIENCE -- Chemistry -- General; Composite materials; Engineered wood; Natural products; Electronic books; Electronic books